Solitary pulmonary nodule - Ferrari, Ivonne; Estapé, Gonzalo; Torterolo, Edgardo; Lizaso, Isabel; Goller, Wolfgang (Cirugía del Uruguay, 1980)
Considerations are made about the different etiology of solitary lung nodules, pointing out in particular the difficulty of diagnosis. The importance of the association of clinical radiology, endoscopy, exploratory thoracotomy, and extemporaneous biopsy is emphasized. to · achieve dichi, end. Three histories are exposed; ls type 'that: document what was indicated.